2012
DOI: 10.1590/s0100-69162012000300011
|View full text |Cite
|
Sign up to set email alerts
|

Uniformidade de aplicação de água de equipamentos autopropelidos de irrigação com aspersores de perfil radial triangular, elíptico e retangular

Abstract: RESUMO:Este trabalho apresenta resultados de simulações digitais da uniformidade de aplicação de água de sistemas autopropelidos de irrigação, para a condição de ausência de ventos. Nas simulações foram considerados aspersores com perfis radiais de distribuição de água tipo triangular, elíptico e retangular, operando sob diferentes combinações de ângulo de giro (de 180 até 360º) e espaçamento entre carreadores (de 0 a 100% do diâmetro molhado -DM). Os resultados das simulações foram apresentados em três grupos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
3
1
1
Order By: Relevance
“…Compared to typical behavior found in the literature for the geometric shape of the curve formed by the radial profile (triangular, rectangular and elliptical) cited by Prado et al [26], it was not observed for the sprinkler Super 10 in Figures 4-6, any of three behaviors, but the combination of all. Similar behavior was observed by Stambouli et al [27] using the sprinkler RC130-BY manufactured by Riegos Costa.…”
Section: Radial Profile and Uniformity Of Water Distributioncontrasting
confidence: 72%
“…Compared to typical behavior found in the literature for the geometric shape of the curve formed by the radial profile (triangular, rectangular and elliptical) cited by Prado et al [26], it was not observed for the sprinkler Super 10 in Figures 4-6, any of three behaviors, but the combination of all. Similar behavior was observed by Stambouli et al [27] using the sprinkler RC130-BY manufactured by Riegos Costa.…”
Section: Radial Profile and Uniformity Of Water Distributioncontrasting
confidence: 72%
“…As observed by Prado et al (2012) and presented in Figure 4, in the strip spacing range (60 to 70% of the WD) indicated by manufacturers of traveler irrigation machines, sprinkler wetted angles from 210 to 330º, symmetrically adjusted to the travel path (β = 0), give CU values less than 80%. However, some asymmetry adjustments, especially for wetted angles of 270, 300, and 330°, may considerably increase the CU values (Figure 4).…”
Section: Resultsmentioning
confidence: 64%
“…On the other hand, for a wind speed condition of 1.5 m s -1 , regardless of wind direction, water distribution uniformity improves in the irrigation strip widths around 70% of the WD (Figures 5, 6, and 7). According to Keller & Bliesner (1990) and Prado et al (2012), water application profiles transverse to the travel path with uniform or rectangular shapes result in high CU values for spacings near the WD for no-wind conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prado et al (2012) observaram que independentemente do tipo de perfil radial de distribuição de água, ângulos de giro próximos de 270º proporcionam baixos condições de campo. Porém, necessitam de alta pressão de serviço e, consequente, elevado consumo de energia, além de terem a uniformidade de aplicação de água muito afetada pelas condições de operação, em especial pelo vento (BERNARDO et al, 2008).…”
Section: Resultsunclassified